From insertion to multicomponent coupling: temperature dependent reactions of arynes with aliphatic alcohols - Thangaraj, Manikandan; Bhojgude, Sachin Suresh; Mane, Manoj V.; Biju, Akkattu T. (Chemical Communications, 2016)
The temperature dependent selectivity switch in the reaction of arynes with aliphatic alcohols in THF has been reported. At -20 degrees C, arynes smoothly insert into the O-H bond of alcohols to form alkyl aryl ethers. Interestingly, at 60 degrees C, a highly selective multicomponent coupling occurs with the solvent THF acting as the nucleophilic trigger affording (4-(alkoxy)butoxy)arenes.